Capacity Building and Community Empowerment Strategies Based on Local Wisdom: A Case Study of Cimande Village - Ishak, Riani Prihatini (Institut Pariwisata Trisakti, 2024)
This study explores strategies for capacity building and community empowerment in Cimande Village, focusing on the roles of the Tourism Awareness Group (Pokdarwis) and Micro, Small, and Medium Enterprises (MSMEs). The primary objective is to assess how local wisdom can be leveraged to enhance the economic and social wellbeing of the community through tourism. Using qualitative research methods, including in-depth interviews and direct observation, the study applies a SWOT analysis to identify internal and external factors affecting the success of tourism development in Cimande Village. Key findings highlight significant barriers such as limited entrepreneurial knowledge, inadequate product innovation, and insufficient use of digital marketing. Conversely, strengths include rich local culture, strong community participation, and government support. The discussion focuses on strategies to improve capacity building, particularly through education, infrastructure development, and stronger collaboration with the private sector. The study concludes that sustainable tourism development in Cimande depends heavily on continuous training and capacity enhancement, particularly in product innovation and digital marketing. Recommendations include establishing more formalized training programs for Pokdarwis and MSME operators, improving access to capital, and increasing efforts to secure business legality and certifications. Keywords: capacity strengthening, community empowerment, local wisdom, pokdarwis, MSMEs, Cimande Village, sustainable tourism